Lithium fluoride ceramic target material as well as preparation method and application thereof

Through the combination of cold isostatic molding and pressure-free sintering, the applied pressure and sintering conditions are regulated, and the low density and hole problems in the preparation of lithium fluoride ceramic targets are solved, and a high-density lithium fluoride ceramic target is obtained. material.

CN119430943AInactive Publication Date: 2025-02-14KONFOONG MATERIALS INTERNATIONAL CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411593475.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

It is difficult to effectively prepare high-density lithium fluoride ceramic targets in the prior art, and pores and foaming are easily generated during the sintering process.

Method used

A high-density lithium fluoride ceramic target material is prepared by regulating the applied pressure of cold isostatic molding and pressure-free sintering, by controlling the target temperature and insulation time of cold isostatic molding.

Benefits of technology

A lithium fluoride ceramic target with a relative density of ≥93% was successfully obtained, filling the current technology gap and improving the density and performance of the ceramic target.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a lithium fluoride ceramic target as well as a preparation method and application thereof. The preparation method comprises the steps of mixing, dry pressing, cold isostatic pressing, pressureless sintering and post-treatment which are carried out in sequence, wherein the applied pressure of the cold isostatic pressing forming is 50 to 300 MPa; the target temperature of pressureless sintering is 550-750 DEG C, and the heat preservation time is longer than or equal to 1 h. The high-density lithium fluoride ceramic target material is successfully prepared in a cold isostatic pressing and pressureless sintering combined mode, and the current technical blank is filled.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of target material preparation, and relates to a lithium fluoride ceramic target material, and in particular to a lithium fluoride ceramic target material and a preparation method and application thereof. Background Art

[0002] In OLED (organic light-emitting diode) products, the introduction of LiF film can accelerate the excitation and injection of carriers, thereby improving device performance; in the SEI layer (solid electrolyte interface) of lithium batteries, the presence of LiF interface film can effectively inhibit lithium metal deposition and SEI film breakage during charge and discharge cycles. At present, such films can be prepared by bombarding LiF ceramic targets with charged particles, but there are few high-purity LiF ceramic target preparation technologies reported at home and abroad.

[0003] As we all know, the preparation of ceramic materials mainly involves powder pressing and sintering processes. Due to the low surface free energy of fluorides, it is difficult to fully densify ceramic materials by relying solely on temperature as a sintering aid, and other sintering driving forces are needed to assist the densification of ceramics. In addition, when LiF is sintered alone, fluorine-containing gas will be produced during the sintering process, causing significant foaming of the sintered body and the formation of holes inside. Therefore, existing preparation methods such as sintering aid-assisted pressureless sintering, vacuum hot pressing sintering, cold sintering and other technologies are only for ceramic materials such as calcium fluoride and barium fluoride, so the development of lithium fluoride ceramic target preparation technology is urgent.

[0004] CN115215659A discloses a sintered body for radiation shielding material, radiation shielding material and a method for manufacturing the same, wherein MgF is added to 5-99wt% LiF powder. 2 , CaF 2 , AlF 3 , KF, NaF, YF 3 One or more of the above, with the addition amount being 1-95wt%; through powder mixing, dry pressing, CIP molding, temporary sintering process, primary sintering process, and secondary sintering process, a fluoride sintered body with a density of more than 92% is finally obtained.

[0005] CN105218109A discloses a fluoride ceramic crucible and a manufacturing method thereof. The method comprises adding 0.5-3% of a sintering aid to one or more powders of calcium fluoride, magnesium fluoride, sodium fluoride, potassium fluoride, lithium fluoride, erbium fluoride, rubidium fluoride and lanthanum fluoride, mixing the powders for 16-24 hours, sieving through an 80-mesh sieve, performing vacuum sintering at 900-1200°C after CIP molding at 100-200MPa; and finally, performing hot isostatic pressing sintering at 800-1100°C to obtain a crucible with a density of 2.6-3.2g / cm 3 Fluoride ceramic crucible.

[0006] CN112876251A discloses a high-performance low-dielectric microwave ceramic and method based on cold sintering technology, which is used to prepare BaF 2 Deionized water <25wt% was added to the powder, and after cold sintering by a hot press, the powder was kept at 950°C for 3h at a heating rate of 5°C / min, and finally a transparent ceramic with a density of about 92% was obtained.

[0007] It can be seen that although the existing technology discloses the preparation of fluoride ceramics using vacuum hot pressing sintering, cold sintering and other technologies, there is almost no mention of the preparation method of lithium fluoride ceramic targets, so there is an urgent need to fill this technical gap. Summary of the invention

[0008] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a lithium fluoride ceramic target material and a preparation method and application thereof, and successfully prepare a high-density lithium fluoride ceramic target material by combining cold isostatic pressing and pressureless sintering, filling the current technical gap.

[0009] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0010] In a first aspect, the present invention provides a method for preparing a lithium fluoride ceramic target, the preparation method comprising mixing, dry pressing, cold isostatic pressing, pressureless sintering and post-treatment performed in sequence.

[0011] Among them, the applied pressure of the cold isostatic pressing is 50-300MPa, for example, it can be 50MPa, 100MPa, 150MPa, 200MPa, 250MPa or 300MPa, the target temperature of the pressureless sintering is 550-750℃, for example, it can be 550℃, 600℃, 650℃, 700℃ or 750℃, and the holding time is ≥1h, for example, it can be 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h or 10h, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0012] In the present invention, the applied pressure of the cold isostatic pressing has an important influence on the forming, densification degree and final target performance of the ceramic target. When the applied pressure is lower than 50MPa, the gaps between the powder particles cannot be effectively eliminated due to the low pressure, which affects the subsequent densification process after sintering; when the applied pressure is higher than 300MPa, the interaction force between the powder particles will be enhanced, which may easily lead to excessive extrusion and deformation between the particles, and then cause internal defects such as pores and cracks. In addition, excessive pressure will increase the risk of equipment failure and damage.

[0013] The present invention specifically limits the target temperature of pressureless sintering to 550-750°C. This is because: when the target temperature is lower than 550°C, the excessively low sintering temperature slows down the diffusion and migration speed between the powder particles, and some powder particles fail to form a good bond; when the target temperature is higher than 750°C, excessive diffusion and migration will occur between the powder particles, forming a large amount of liquid phase, increasing the viscosity of the sintered body, slowing down the particle rearrangement, affecting the gas discharge, and thus affecting its density and performance.

[0014] In addition, the present invention limits the heat preservation time to more than 1 hour, which can ensure the uniformity and integrity of the internal reaction of the ceramic material and avoid the situation of partial unsintering or insufficient sintering.

[0015] It can be seen that the preparation method provided by the present invention improves the relative density of the ceramic green body by regulating the applied pressure of cold isostatic pressing without adding any sintering aids; at the same time, by strictly limiting the target temperature and holding time in the pressureless sintering process to promote the sintering densification process of the sample, a high-density lithium fluoride ceramic target is finally obtained, filling the current technical gap.

[0016] Preferably, the powder is dried before mixing.

[0017] Preferably, the powder drying comprises: weighing lithium fluoride powder and drying it in a vacuum oven.

[0018] Preferably, the drying temperature is 60-100°C, for example, it can be 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C or 100°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0019] Preferably, the drying time is 12-36 h, for example, it can be 12 h, 14 h, 16 h, 18 h, 20 h, 22 h, 24 h, 26 h, 28 h, 30 h, 32 h, 34 h or 36 h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0020] Preferably, the mixing comprises: weighing the dried lithium fluoride powder, adding a binder and mixing evenly.

[0021] The binder added to the lithium fluoride powder of the present invention promotes the close bonding between the ceramic powder particles through its bonding force, thereby improving the strength of the ceramic body. This enhanced bonding force helps to reduce cracks and deformation during the preparation process, so that the final ceramic product has better performance.

[0022] Preferably, the binder comprises a polyvinyl alcohol (PVA) solution with a concentration of 1-5wt%, for example, it can be 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt% or 5wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0023] Preferably, the mass fraction of polyvinyl alcohol after mixing is 0.5-5wt%, for example, it can be 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt% or 5wt%, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0024] Preferably, the dry pressing is carried out in a stainless steel mould.

[0025] Preferably, the applied pressure of the dry pressing is 30-40MPa, for example, it can be 30MPa, 31MPa, 32MPa, 33MPa, 34MPa, 35MPa, 36MPa, 37MPa, 38MPa, 39MPa or 40MPa, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0026] Preferably, the holding time of the cold isostatic pressing is 30-60 min, for example, it can be 30 min, 35 min, 40 min, 45 min, 50 min, 55 min or 60 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0027] Preferably, the pressureless sintering is performed in a muffle furnace in an air atmosphere.

[0028] Preferably, the heating rate of the pressureless sintering is 1-10°C / min, for example, it can be 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min or 10°C / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0029] The present invention specifically limits the heating rate of pressureless sintering to 1-10°C / min, because the heating rate within this range will guide the particles to grow gradually during the sintering process, and the pores have enough time to migrate to the particle interface and discharge, thereby improving the density of the target blank obtained. However, when the heating rate is lower than 1°C / min, the too low heating rate will prolong the sintering cycle, resulting in unnecessary increase in energy consumption and production costs; when the heating rate is higher than 10°C / min, the shrinkage curve will shift to the high temperature direction, resulting in the mass transfer between substances not being completed in time, the pores cannot be discharged in time, and the crystal phase inside the ceramic cannot grow fully, resulting in an increase in the pores of the ceramic and a decrease in density.

[0030] Preferably, the holding time of the pressureless sintering is 1-10 h, for example, it can be 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h or 10 h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0031] Preferably, the post-processing comprises machining.

[0032] As a preferred technical solution of the first aspect of the present invention, the preparation method comprises the following steps:

[0033] (1) Weigh lithium fluoride powder and dry it in a vacuum oven at 60-100° C. for 12-36 hours;

[0034] (2) adding a polyvinyl alcohol solution with a concentration of 1-5 wt % to the lithium fluoride powder after sieving through 100-300 meshes and mixing them evenly, wherein the mass fraction of the polyvinyl alcohol after mixing is 0.5-5 wt %;

[0035] (3) transferring the mixed powder to a stainless steel mold for dry pressing, and controlling the applied pressure to be 30-40 MPa;

[0036] (4) performing cold isostatic pressing on the sample obtained by dry pressing, and controlling the applied pressure to be 50-300 MPa and the holding time to be 30-60 min;

[0037] (5) transferring the green blank obtained by cold isostatic pressing to a muffle furnace in an air atmosphere for pressureless sintering, and controlling the heating rate to be 1-10°C / min, the target temperature to be 550-750°C, and the holding time to be 1-10h;

[0038] (6) Mechanically process the target blank obtained by pressureless sintering to obtain a lithium fluoride ceramic target.

[0039] In a second aspect, the present invention provides a lithium fluoride ceramic target prepared by the preparation method described in the first aspect, wherein the relative density of the lithium fluoride ceramic target is ≥93%, for example, it can be 93%, 93.5%, 94%, 94.5%, 95%, 95.5%, 96%, 96.5%, 97%, 97.5% or 98%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0040] In a third aspect, the present invention provides an application of the lithium fluoride ceramic target material as described in the second aspect, wherein the lithium fluoride ceramic target material is used for magnetron sputtering deposition of lithium fluoride thin films.

[0041] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0042] Compared with the prior art, the present invention has the following beneficial effects:

[0043] The preparation method provided by the present invention improves the relative density of the ceramic green body by regulating the applied pressure of cold isostatic pressing without adding any sintering aids; at the same time, by strictly limiting the target temperature and holding time in the pressureless sintering process to promote the sintering densification process of the sample, a high-density lithium fluoride ceramic target is finally obtained, filling the current technical gap. DETAILED DESCRIPTION

[0044] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only used to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0045] Example 1

[0046] This embodiment provides a lithium fluoride ceramic target and a preparation method thereof, the preparation method comprising the following steps:

[0047] (1) Weigh lithium fluoride powder and dry it in a vacuum oven at 80° C. for 24 h;

[0048] (2) adding a 3 wt % polyvinyl alcohol solution to the lithium fluoride powder after sieving through 200 meshes and mixing the mixture evenly, wherein the mass fraction of the polyvinyl alcohol after mixing is 2.5 wt %;

[0049] (3) The mixed powder was transferred to a stainless steel mold for dry pressing, and the applied pressure was controlled to be 35 MPa;

[0050] (4) performing cold isostatic pressing on the sample obtained by dry pressing, and controlling the applied pressure to be 100 MPa and the holding time to be 45 min;

[0051] (5) The green blank obtained by cold isostatic pressing was transferred to a muffle furnace in an air atmosphere for pressureless sintering, and the heating rate was controlled to be 5°C / min, the target temperature was 600°C, and the holding time was 3h;

[0052] (6) Mechanically process the target blank obtained by pressureless sintering to obtain a lithium fluoride ceramic target.

[0053] Example 2

[0054] This embodiment provides a lithium fluoride ceramic target and a preparation method thereof, the preparation method comprising the following steps:

[0055] (1) Weigh lithium fluoride powder and dry it in a vacuum oven at 60° C. for 36 h;

[0056] (2) adding a polyvinyl alcohol solution with a concentration of 1 wt % to the lithium fluoride powder after sieving through 100 meshes and mixing them evenly, wherein the mass fraction of the polyvinyl alcohol after mixing is 0.5 wt %;

[0057] (3) The mixed powder was transferred to a stainless steel mold for dry pressing, and the applied pressure was controlled to be 30 MPa;

[0058] (4) performing cold isostatic pressing on the sample obtained by dry pressing, and controlling the applied pressure to be 150 MPa and the holding time to be 60 min;

[0059] (5) The green blank obtained by cold isostatic pressing was transferred to a muffle furnace in an air atmosphere for pressureless sintering, and the heating rate was controlled to be 1°C / min, the target temperature was 650°C, and the holding time was 5h;

[0060] (6) Mechanically process the target blank obtained by pressureless sintering to obtain a lithium fluoride ceramic target.

[0061] Example 3

[0062] This embodiment provides a lithium fluoride ceramic target and a preparation method thereof, the preparation method comprising the following steps:

[0063] (1) Weigh lithium fluoride powder and dry it in a vacuum oven at 100° C. for 12 h;

[0064] (2) adding a 5 wt % polyvinyl alcohol solution to the lithium fluoride powder after sieving through 300 meshes and mixing the mixture evenly, wherein the mass fraction of the polyvinyl alcohol after mixing is 3.5 wt %;

[0065] (3) The mixed powder was transferred to a stainless steel mold for dry pressing, and the applied pressure was controlled to be 40 MPa;

[0066] (4) performing cold isostatic pressing on the sample obtained by dry pressing, and controlling the applied pressure to be 200 MPa and the holding time to be 30 min;

[0067] (5) The green blank obtained by cold isostatic pressing was transferred to a muffle furnace in an air atmosphere for pressureless sintering, and the heating rate was controlled to be 8°C / min, the target temperature was 680°C, and the holding time was 1h;

[0068] (6) Mechanically process the target blank obtained by pressureless sintering to obtain a lithium fluoride ceramic target.

[0069] Example 4

[0070] This embodiment provides a lithium fluoride ceramic target and a preparation method thereof, the preparation method comprising the following steps:

[0071] (1) Weigh lithium fluoride powder and dry it in a vacuum oven at 80° C. for 24 h;

[0072] (2) adding a 3 wt % polyvinyl alcohol solution to the lithium fluoride powder after sieving through 200 meshes and mixing the mixture evenly, wherein the mass fraction of the polyvinyl alcohol after mixing is 2.5 wt %;

[0073] (3) The mixed powder was transferred to a stainless steel mold for dry pressing, and the applied pressure was controlled to be 35 MPa;

[0074] (4) performing cold isostatic pressing on the sample obtained by dry pressing, and controlling the applied pressure to be 250 MPa and the holding time to be 60 min;

[0075] (5) The green blank obtained by cold isostatic pressing was transferred to a muffle furnace in an air atmosphere for pressureless sintering, and the heating rate was controlled to be 1°C / min, the target temperature was 700°C, and the holding time was 6h;

[0076] (6) Mechanically process the target blank obtained by pressureless sintering to obtain a lithium fluoride ceramic target.

[0077] Example 5

[0078] This embodiment provides a lithium fluoride ceramic target and a preparation method thereof, the preparation method comprising the following steps:

[0079] (1) Weigh lithium fluoride powder and dry it in a vacuum oven at 80° C. for 24 h;

[0080] (2) adding a 3 wt % polyvinyl alcohol solution to the lithium fluoride powder after sieving through 200 meshes and mixing the mixture evenly, wherein the mass fraction of the polyvinyl alcohol after mixing is 2.5 wt %;

[0081] (3) The mixed powder was transferred to a stainless steel mold for dry pressing, and the applied pressure was controlled to be 35 MPa;

[0082] (4) performing cold isostatic pressing on the sample obtained by dry pressing, and controlling the applied pressure to be 300 MPa and the holding time to be 30 min;

[0083] (5) The green blank obtained by cold isostatic pressing was transferred to a muffle furnace in an air atmosphere for pressureless sintering, and the heating rate was controlled to be 10°C / min, the target temperature was 720°C, and the holding time was 1h;

[0084] (6) Mechanically process the target blank obtained by pressureless sintering to obtain a lithium fluoride ceramic target.

[0085] Comparative Example 1

[0086] This comparative example provides a lithium fluoride ceramic target material and a preparation method thereof. Except that the applied pressure of the cold isostatic pressing in step (4) is changed to 30 MPa, the remaining steps and conditions are the same as those in Example 1, and thus are not described in detail here.

[0087] Comparative Example 2

[0088] This comparative example provides a lithium fluoride ceramic target and a preparation method thereof. Except that the target temperature of the pressureless sintering in step (5) is changed to 500° C., the remaining steps and conditions are the same as those in Example 1, and thus are not described in detail here.

[0089] Comparative Example 3

[0090] This comparative example provides a lithium fluoride ceramic target and a preparation method thereof. Except that the holding time of the pressureless sintering in step (5) is changed to 0.5 h, the remaining steps and conditions are the same as those in Example 1, and thus are not described in detail here.

[0091] After testing, the relative density and surface quality of the lithium fluoride ceramic targets obtained in Examples 1-5 and Comparative Examples 1-3 are shown in Table 1 below.

[0092] Table 1

[0093] Lithium fluoride ceramic target Is there any crack after CIP? Relative density Example 1 no 93% Example 2 no 93.6% Example 3 no 94% Example 4 no 94.2% Example 5 no 94.1% Comparative Example 1 no 85% Comparative Example 2 no 82% Comparative Example 3 no 88%

[0094] It can be seen that the preparation method provided by the present invention improves the relative density of the ceramic green body by regulating the applied pressure of cold isostatic pressing without adding any sintering aids; at the same time, by strictly limiting the target temperature and holding time in the pressureless sintering process to promote the sintering densification process of the sample, a high-density lithium fluoride ceramic target is finally obtained, filling the current technical gap.

[0095] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a lithium fluoride ceramic target, characterized in that: The preparation method comprises mixing, dry pressing, cold isostatic pressing, pressureless sintering and post-processing in sequence; The applied pressure of the cold isostatic pressing is 50-300 MPa; the target temperature of the pressureless sintering is 550-750° C., and the holding time is ≥1h.

2. The preparation method according to claim 1, characterized in that: Powder drying is performed before the mixing; Preferably, the powder drying comprises: weighing lithium fluoride powder and drying it in a vacuum oven; Preferably, the drying temperature is 60-100°C; Preferably, the drying time is 12-36 hours.

3. The preparation method according to claim 1 or 2, characterized in that: The mixing comprises: weighing the dried lithium fluoride powder, adding a binder and mixing evenly; Preferably, the binder comprises a polyvinyl alcohol solution having a concentration of 1-5wt%; Preferably, the mass fraction of the polyvinyl alcohol after mixing is 0.5-5wt%.

4. The preparation method according to any one of claims 1 to 3, characterized in that: The dry pressing is carried out in a stainless steel mold; Preferably, the applied pressure of the dry pressing is 30-40 MPa.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The holding time of the cold isostatic pressing is 30-60 minutes.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The pressureless sintering is carried out in a muffle furnace in an air atmosphere; Preferably, the heating rate of the pressureless sintering is 1-10°C / min; Preferably, the holding time of the pressureless sintering is 1-10h.

7. The preparation method according to any one of claims 1 to 6, characterized in that: The post-processing includes machining.

8. The preparation method according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: (1) Weigh lithium fluoride powder and dry it in a vacuum oven at 60-100° C. for 12-36 hours; (2) adding a polyvinyl alcohol solution with a concentration of 1-5 wt % to the lithium fluoride powder after sieving through 100-300 meshes and mixing them evenly, wherein the mass fraction of the polyvinyl alcohol after mixing is 0.5-5 wt %; (3) transferring the mixed powder to a stainless steel mold for dry pressing, and controlling the applied pressure to be 30-40 MPa; (4) performing cold isostatic pressing on the sample obtained by dry pressing, and controlling the applied pressure to be 50-300 MPa and the holding time to be 30-60 min; (5) transferring the green blank obtained by cold isostatic pressing to a muffle furnace in an air atmosphere for pressureless sintering, and controlling the heating rate to be 1-10°C / min, the target temperature to be 550-750°C, and the holding time to be 1-10h; (6) Mechanically process the target blank obtained by pressureless sintering to obtain a lithium fluoride ceramic target.

9. A lithium fluoride ceramic target prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The relative density of the lithium fluoride ceramic target material is ≥93%.

10. An application of the lithium fluoride ceramic target material as claimed in claim 9, characterized in that: The lithium fluoride ceramic target is used for depositing lithium fluoride thin film by magnetron sputtering.

Citation Information

Patent Citations

  • Fluoride ceramic crucible and preparation method thereof

    CN105218109A

  • High-performance low-dielectric microwave ceramic prepared based on cold sintering technology and method

    CN112876251A

  • Sintered body for radiation shielding material, radiation shielding material, and method for producing same

    CN115215659A

  • Magnesium fluoride composite ceramic and preparation method thereof

    CN115872746A

  • Molybdenum tantalum oxide target material and preparation method and application thereof

    CN116332645A